Pengembangan Aplikasi Laporan Keuangan Berbasis Database Server - Wensen, Viltie; Mesdilah, Filadelfia; Kondoj, Marike (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Manado, 2024)
Financial reports are an important element in an organization to manage finances and provide information to internal and external parties. However, the process of making financial reports is often time-consuming, error-prone, and difficult to access. To overcome these problems, this research aims to develop a database server-based financial report application. This application is expected to assist organizations in preparing financial reports automatically and accurately, facilitate access and analysis of financial data, and improve the efficiency and effectiveness of financial management. This research uses the waterfall method, which includes the stages of literature study, observation, interviews, questionnaires, and empirical data. Through this approach, each stage is expected to be carried out systematically and structured, resulting in an application that is reliable and in accordance with user needs. The expected result of this research is the creation of an application with a dashboard feature for financial data visualization, which allows users to monitor the organization's financial condition in real-time. In addition, this application will also provide access to financial data through a database server-based web browser, making it easier for users to access and analyze financial data anytime and anywhere. Thus, this application is expected to be an effective solution in managing financial reports for organizations, increasing transparency, and supporting better decision making.